Serapan NPK Kelapa Sawit dengan Aplikasi Dregs dan Trichoderma sp pada Pembibitan Awal di Medium Gambut - Wardati '; Yetti Elfina (Jurnal Sagu, 2008)
The objective of this research was to study the influence of interaction between primary factors of trichoderma sp and dregs to N, P, K absorption in oil palm seedling at peat medium in pre nursery. It is conducted from September 2006 to februari 2007. The parameters of this research were N, P, K content of soil peat; N, P, K absorption of plant, shoot dry weight and root dry weight. The sesult indicated that the treatment of trichoderma sp and dregs increased N, P, K availability in peat medium and N, P, K absorption of palm seedling.